Social malaise and Cultural Implication in Aravind Adiga‘s the White Tiger-A Thematic Study - Senthilkumar, S. (International Journal of Psychosocial Rehabilitation, 2020)
This paper attempts to explore how Aravind Adiga, in his debut novel titled The White Tiger depicts the social malaise and cultural conflict in Indian society by raising the essential and pertinent issues like poverty, hunger, oppression, social inequalities and injustice based on the grounds of caste, religion and class through the story of a man who rose from a humble background to achieve success in the upper echelons of Indian society. Also, this paper describes how Adiga portrays the chaos of the current social structure with stark realities like the rich dominating the poor and ‘the Rooster Coop’ revolt. Breaking out of the Rooster Coop is nearly impossible and requires highly unethical actions including murder and betrayal of one’s family, which keeps almost everyone trapped in the Rooster Coop indefinitely. Adiga indirectly suggests reforms in social, economic and political system by eradicating individual vices, social evils and disintegrating systems. Most of the issues raised by Adiga are prevalent in third world nations and they are to be understood with their complexity and addressed properly.